Evaluating the economic viability of growing winter hybrid rye to feed and bed organic pigs - Li, Yuzhi Z.; Kavanagh, Megan; Lazarus, William F.; Lima, Gabriella; Hilbrands, Adrienne M.; Wilson, Melissa; Garcia y Garcia, Axel; Tallaksen, Joel; Johnston, Lee J. (Frontiers in Animal Science, 2025)
The high production cost is one of the biggest challenges to the sustainability of organic pig production. Growing winter hybrid rye to feed and bed organic pigs might be a strategy to reduce production costs. In this study, we evaluated the economic viability of integrating rye into an organic swine production system. Winter hybrid rye was grown organically over two years, yielding an average of 5,430 kg/ha of grain and 3,135 kg/ha of straw. Replacing 50% of corn with rye grain in feed and using rye straw as bedding materials did not negatively impact growth performance of organic growing-finishing pigs. This replacement resulted in $14/pig savings on feed and bedding and increased net return for a swine enterprise (swine savings) by $6/pig, compared with feeding corn soybean meal diets and bedding with wheat straw. Sensitivity analysis was conducted to evaluate how crop net returns may vary with changes in market prices, yield, and production costs of a rye crop. Results indicate that for farmers to be profitable by growing rye as a cash crop, the minimal price of rye grain needs to be $0.24/kg at a yield of around 5,000 kg/ha with production costs of $1,642/ha. Growing rye to feed and bed organic pigs can offset crop net returns, resulting in $319 to $666/ha of crop net returns and swine savings for the combined crop and swine enterprise. These results suggest that integrating hybrid rye into organic swine production is economically viable under the circumstances described in this study and can benefit both crop and pig farmers.